Principles of climatology - Renneboog, Richard (Salem Press, a division of EBSCO Information Services, Inc. ; Grey House Publishing, 2018)
Introduces students and researchers to the fundamentals of climatology using easy-to-understand language for a solid background and a deeper understanding and appreciation of this important and evolving subject.